Pro-health Behaviours in Time Budget of Ex-cyclists - Magdalena Bentkowska (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2019)
The study involved 50 ex-cyclists at age 22-66, there were 17 women and 33 men. This survey-based study was performed using two standardized tools: Health Behaviour Inventory (IZZ) and The questionnaire on daily routines (chronocard).The most of the studied group (58%) undertook pro-health behaviours at the median level, 24% presented the maximum level of health behaviours, and the smallest studied group (18%) presented the minimum level of IZZ. It showed that gender didn't influence the health behaviour of ex-cyclists (p=0,784). An amount of time for different activities (work/study, activities at home, relax, entertainment, physical activity and others) is different during each weekdays. The dominance in the time budget of ex-cyclists was work (study).The most of the leisure time, the studied group spent for amusements and the less for relax and physical activity.The dominance of the studied group were in median and minimum level of health behaviours with the most escalated behaviours in positive mental attitude and lower in nutritional habits, prophylactic behaviours and healthy habits. The studied group presented very restricted pro-healthy lifestyle.